The politics of bureau reform in Sub-Saharan Africa - Caulfield, Janice L. (2006)
This article focuses on sub-Saharan Africa and its recent history of state sector decentralisation reforms. Over the last ten to fifteen years, new forms of state organisation have emerged reflecting a policy preference for bureau downsizing and devolution. These include semi-autonomous executive agencies, public-private partnerships in infrastructure development, partial privatisations of utilities and performance contracting arrangements between purchasers and providers. Reform policies are, however, heavily conditioned by bilateral and multilateral donors. The limited success of bureau reforms in the region has been explained by others as either a problem of institutional capacity or the absence of grassroots democracy. This article takes a different stance, arguing that reforms are highly political and resisted not only by politicians but also by an aware and sceptical public. A selection of case studies illustrates these reform trends and problems of implementation. The article also draws attention to infra-regional differences between a francophone West Africa and English speaking East Africa. - Reproduced.
Keywords: Administrative reform - Sub-Saharan Africa; Administrative reform